Banana Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Ian Maguire (EDIS, 2006)
Revised! HS-10, a 13-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Ian Maguire, provides general information to Florida homeowners for growing bananas. Includes tables of cultivars available in south Florida, cultural calendar, fertilizer program, and nutrient values for raw banana fruit. This version expands and updates information throughout, while narrowing the content to specifically address the needs of a homeowner audience. Published by the UF Department of Horticultural Sciences, September 2005.